Short Communication Diagnosis and Efficacy of Brucella abortus Strain RB51 in Experimentally Inoculated Sprague - Dawley Rats Using Dot Blot Assay - Rahman, M. S.; Baek, B. K. (Biological Sciences - PJSIR, 2007)
Sprague-Dawley (SD) rats were experi mental l y i nocu lated wi th Bruce/la abortus strain R l35 I and challenged 4 weeks post i nocul ation w ith B. abortus bi otype I . Mon itori ng of the sera by dot-blot assay and cl i n ical exam i nation of the rats revealed the h ighest i m m une response. SR B5 I was isolated from the blood of all i nocu l ated rats u nti l !"week post i noculation wi thout any cl i nical sign. f t is concl uded th at SR B5 I produces i mm u n i ty i n SD rats and i nduces protection against B. abortus biotype I and that Dot Blot Assay is an easy, less time consumi ng and correct-resul t readi ng test.